2016
DOI: 10.1113/ep085955
|View full text |Cite
|
Sign up to set email alerts
|

Warm hands, cold heart: progressive whole‐body cooling increases warm thermosensitivity of human hands and feet in a dose‐dependent fashion

Abstract: Edited by: Paul Fadel New Findings r What is the central question of this study?Investigations on inhibitory/facilitatory modulation of vision, touch and pain show that conditioning stimuli outside the receptive field of testing stimuli modulate the central processing of visual, touch and painful stimuli. We asked whether contextual modulation also exists in human temperature integration. r What is the main finding and its importance?Progressive decreases in whole-body mean skin temperature (the conditioning s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…Finally, we have recently demonstrated that changes in whole‐body thermal state can modulate local thermal sensitivity (Filingeri et al . ) and so it cannot be excluded that exercise‐induced changes in mean T sk and T core could have also shifted local thermal sensitivity (Cabanac et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we have recently demonstrated that changes in whole‐body thermal state can modulate local thermal sensitivity (Filingeri et al . ) and so it cannot be excluded that exercise‐induced changes in mean T sk and T core could have also shifted local thermal sensitivity (Cabanac et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…22ᵒC) recorded in our CTR group. Furthermore, we recently discovered that whole-body thermal stress modulates local skin thermosensitivity in healthy adults (Filingeri et al, 2017a) via central mechanisms similar to those underlying endogenous analgesia (Ossipov et al, 2010). Hence, it cannot be excluded that an interaction between pathological (i.e.…”
Section: Magnitude Estimation Of Warm and Cold Stimulimentioning
confidence: 99%
“…During this session, we used a novel quantitative sensory testing paradigm to assess perceived magnitude of cold and warm temperature stimuli applied to the dorsum of the hand. Our novel quantitative sensory test of afferent thermosensory function is based on the one we recently developed and tested in healthy individuals to assess the effects of whole-body thermal stress on local skin thermosensitivity (Filingeri et al, 2017a) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations